Enhanced Mechanism of Nano Zero-Valent Iron Activated Persulfate for Persistent Organic Pollutants in the Environment: A Critical Review - Iribagiza, Marie Rose; Li, Ting; Liang, Wenjing; Wu, Yuanyuan; Zhu, Fang (The Global Environmental Engineers, 2022)
The advanced oxidation process based on persulfate has a broad application prospect in the remediation of organic pollutants. As an effective, low-cost and environmentally friendly material, nano-zero-valent iron (nZVI) can effectively activate persulfate (nZVI/PS) to generate strongly oxidizing sulfate radical for removing organic pollutants in the environment. In this review, we first clarify the activation pathway of nZVI activated persulfate including direct activation and indirect activation. Direct activation means that the electrons released by nZVI directly participate in the activation of PS; indirect activation means that Fe0 corrodes to generate Fe2+, and Fe2+ further activate the persulfate. Then, the mechanism of nZVI/PS system to degrade organic pollutants including electron transfer, hydrogen extraction and addition reactions are also discussed. Finally, combined with the activation pathway and the mechanism of degrading organic pollutants, we propose several prospects for the future research direction of nZVI activated persulfate. As a result, this review provides a theoretical basis for the nZVI/PS advanced oxidation system to remediate actual sites contaminated with organic pollutants.